1998
DOI: 10.1080/0032472031000150456
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Contraceptive Supply and Demand in Mexican Fertility Decline: Evidence from a Microdemographic Study

Abstract: This paper uses retrospective life history data to assess the impact of family planning services on contraceptive use in a rural Mexican township. Between 1960 and 1990 contraceptive use rose and fertility declined dramatically. Both contraceptive supply and demand factors were influential in these trends. The start of the government-sponsored family planning programme in the late 1970s was associated with a sharp rise in female sterilization and use of the IUD. However, once we controlled for the changing soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…At least since the 1970s, Latin America and Mexico in particular have experienced very rapid, substantial, and nearly linear declines in fertility that occurred in conjunction with educational expansion, increased female labor force participation, and the diffusion of family planning (Brea 2003;Guzman et al 1996;Lindstrom 1998;Parrado 2000). Figure 1 shows that between 1990 and 2006, TFR declined steadily in Latin America/Mexico from 3.2/3.5 to 2.4/2.2 children per woman.…”
Section: Anomalies In Vital Registration Estimates Of Hispanic Fertilitymentioning
confidence: 97%
“…At least since the 1970s, Latin America and Mexico in particular have experienced very rapid, substantial, and nearly linear declines in fertility that occurred in conjunction with educational expansion, increased female labor force participation, and the diffusion of family planning (Brea 2003;Guzman et al 1996;Lindstrom 1998;Parrado 2000). Figure 1 shows that between 1990 and 2006, TFR declined steadily in Latin America/Mexico from 3.2/3.5 to 2.4/2.2 children per woman.…”
Section: Anomalies In Vital Registration Estimates Of Hispanic Fertilitymentioning
confidence: 97%
“…As in their place of origin, colonists live in multigenerational patrilineal, patrilocal hierarchically structured households led by a strong authoritarian figure in charge of most production and distribution decisions. This increase is notable in a country such as Mexico where even in rural areas successful birth control campaigns would lead us to expect increases in age at first birth and reduced fertility in younger women (Lindstrom 1998;Miranda 2006). Households with these family characteristics (Caldwell, 1982;Folbre, 1983;Lesthaeghe, 1980;Mason, 2001;Sutherland et al, 2004), level of technology and productive orientation (Bentley et al, 1993;Boserup, 1985;Caldwell, 1976Caldwell, , 1977Caldwell, , 1982 have been found to want to maximize the number of children.…”
Section: Discussionmentioning
confidence: 99%
“…RC women showed a 2.7-year acceleration in age at first birth, and a reduction of interbirth intervals that increased ASFRs at all ages. This increase is notable in a country such as Mexico where even in rural areas successful birth control campaigns would lead us to expect increases in age at first birth and reduced fertility in younger women (Lindstrom 1998;Miranda 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, a terceira linha que nos guia neste trabalho é a de pensar que o mandato de ter que trabalhar/ produzir práticas de saúde onde está em jogo a sexualidade dos pacientes/usuários, "faz ruído" (Merhy, 2003) Das numerosas hipóteses que poderiam ser formuladas para avançar na compreensão deste fenômeno (Lindstrom, 1998;Marston & Cleland, 2003), aqui temos priorizado -seguindo os desenvolvimentos de Sonia Fleury e outros autores (Palmer et.al., 1999;Lush et.al., 2003) (Tomasevski, 1991). A detenção da transmissão vertical exemplifica mais uma vez a necessidade de articular as duas lógicas.…”
Section: O Caso Da Saúde Reprodutiva Na Cidade De Buenos Airesunclassified